PROMIS measures can be used to assess symptoms and function in long‐term hematopoietic cell transplantation survivors. Issue 4 (26th October 2017) - Shaw, Bronwen E.; Syrjala, Karen L.; Onstad, Lynn E.; Chow, Eric J.; Flowers, Mary E.; Jim, Heather; Baker, K. Scott; Buckley, Sarah; Fairclough, Diane L.; Horowitz, Mary M.; Lee, Stephanie J.
Abstract : BACKGROUND: Patient‐reported outcomes for hematopoietic cell transplantation (HCT) survivors are well characterized with established measures; however, there is little experience with the new, freely available Patient‐Reported Outcomes Measurement Information System (PROMIS) measures in this population. The aim of this study was to compare the performance of the PROMIS measures in the HCT setting with the performance of the commonly used 36‐Item Short Form Health Survey (SF‐36). METHODS: Adult HCT survivors from the Fred Hutchinson Cancer Research Center (n = 4446) were mailed a survey that included the following as part of an annual follow‐up survey: the Patient‐Reported Outcomes Measurement Information System–Global Health (PROMIS‐GH; 10 questions), the 29‐Item Patient‐Reported Outcomes Measurement Information System Profile (PROMIS‐29), and the SF‐36. RESULTS: Both the SF‐36 and PROMIS measures were available for 1634 HCT recipients (503 autologous recipients and 1131 allogeneic recipients). The overall response rate was 46%. The median time after transplantation for allogeneic and autologous recipients was 12.0 years (range, 0.4‐44.1 years) and 6.1 years (range, 0.4‐30.1 years), respectively. With the SF‐36 or PROMIS‐GH, overall physical functioning was somewhat lower in comparison with the general population, but mental functioning was similar. Component and domain scores with similar contents were strongly correlated by Pearson correlation coefficients: the Global Health–Physical and SF‐36 Physical Component Summary scores for autologous ( r = 0.82) and allogeneic recipients ( r = 0.83) and the PROMIS‐29 and SF‐36 physical function, pain, and vitality/fatigue scores for allogeneic (0.87, –0.82, and –0.82, respectively) and autologous recipients (0.84, –0.82, and –0.81, respectively). The correlation between the Global Health–Mental and SF‐36 Mental Component Summary scores was lower (0.70 for autologous recipients and 0.72 for allogeneic recipients). CONCLUSIONS: Physical and mental symptoms and function in autologous and allogeneic HCT survivors can be adequately assessed with PROMIS‐29 and PROMIS‐GH. Cancer 2018;124:841‐9 . © 2017 American Cancer Society . Abstract : The 36‐Item Short Form Health Survey and Patient‐Reported Outcomes Measurement Information System measures are strongly correlated in hematopoietic cell transplantation survivors. Symptoms and functional issues in hematopoietic cell transplantation survivors can be adequately assessed with either the 36‐Item Short Form Health Survey or Patient‐Reported Outcomes Measurement Information System measures.